Development of Partnership-Based Management Model of District Learning Encouragement Center in Nakhon Pathom Province - Nantawisan, Panupong; Intarak , Choomsak; Untaweesin, Apinun (Academic MCU Buriram Journal, 2025)
This research aimed to: 1) examine the Partnership-Based Management Model of District Learning Encouragement Center in Nakhon Pathom Province; 2) design and develop a model; 3) evaluate the model; 4) compare pre-test and post-test results; and 5) assess the model terms of efficiency, effectiveness, and value.The participants in this study consisted of 18 individuals Directors, Teachers, and members of the educational network of the Don Tum District Learning Encouragement Center in Nakhon Pathom Province, selected through purposive sampling. The instruments used for data collection included: a questionnaire on perceived problems, an assessment form for the Partnership-Based Management Model of District Learning Encouragement Centers, an experimental action plan, pretest and post-test evaluation form, and an assessment form measuring efficiency, effectiveness, and value. The quality of these instruments was considered from the content validity and the IOC value. The statistics used for data analysis were frequency, percentage, mean, standard deviation, and t-test. The research results found that: 1) the overall problems of Partnership-Based Management Model of District Learning Encouragement Centers in Nakhon Pathom Province were at a high level. 2) The model developed by the researcher, PCERI Model, consisted of five components: Planning, Cooperation, Execution, Reporting, and Improvement. 3) The model evaluation demonstrated strong content validity, with an IOC values ranging from 0.80 to 1.00. 4) Results from the experimental comparison showed that post-test scores were significantly higher than the pre-test scores, with statistical significance at the .01 level. 5) The application of the model in terms of value, efficiency, and effectiveness were found to be at high levels.